Association between Periodontal Disease and Comorbidities in Saudi's Eastern Province. (17th April 2021) - Madi, Marwa; Abuohashish, Hatem M.; Attia, Dina; AlQahtani, Norah; Alrayes, Nabras; Pavlic, Verica; Bhat, Subraya G.
Abstract : The incidence of periodontal diseases is associated with multiple comorbidities that influence a patient's treatment planning. This study evaluates the relation between periodontal disease and multiple comorbidities reported in the Saudi population from the Eastern province. This study was conducted on 190 patients, who visited the periodontology clinics at Imam Abdulrahman Bin Faisal University, Saudi Arabia. Demographic data, smoking habits, past medical and dental histories, blood pressure, random blood glucose, and recent haemoglobin A1c were recorded. A comprehensive periodontal examination included the number of missing teeth, pocket depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), and mobility of all teeth except third molars. Radiographic bone loss was measured on standardized full-mouth periapical radiographs. Multivariable regression models were calculated aiming to see the association between different comorbidities and alveolar bone loss with confounders controlled. Out of 190 periodontitis patients, 56 (29.5%) were males and 134 (70.5%) were females. More than half of the patients (60%) were between 26 and 50 years, 30% of them had diabetes, and 18% were smokers. The risk of alveolar bone loss was higher in persons who had diabetes and those who had both diabetes and coronary heart disease than those who did not, although the association was not statistically significant (B = 1.26, 95 % CI = − 0.30, 2.82, and B = 2.86, 95 % CI = − 1.25, 6.96, respectively). The risk of alveolar bone loss was significantly higher among persons with diabetes and hypertension (B = 2.82 and 95 % CI = 0.89, 4.75). Collectively, the risk of alveolar bone loss in periodontitis patients increases with diabetes in the presence of other comorbidities regardless of smoking or gender.